2020
DOI: 10.1002/mbo3.1051
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable production of FAEE biodiesel using the oleaginous yeast Yarrowia lipolytica

Abstract: Fatty acid ethyl esters (FAEEs) are fatty acid‐derived molecules and serve as an important form of biodiesel. The oleaginous yeast Yarrowia lipolytica is considered an ideal host platform for the production of fatty acid‐derived products due to its excellent lipid accumulation capacity. In this proof‐of‐principle study, several metabolic engineering strategies were applied for the overproduction of FAEE biodiesel in Y. lipolytica . Here, chromosome‐based co‐overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…[42]. It was observed that the presence of the high percentage of fatty acid (C16-C18 carbon atom in the chain) will seem to be ideal as feedstock for biodiesel [12,17,42]. Producing renewable and environmentally safe biofuel helps in the development of green sustainable energy alternatives [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42]. It was observed that the presence of the high percentage of fatty acid (C16-C18 carbon atom in the chain) will seem to be ideal as feedstock for biodiesel [12,17,42]. Producing renewable and environmentally safe biofuel helps in the development of green sustainable energy alternatives [11].…”
Section: Discussionmentioning
confidence: 99%
“…This type of cheaper carbon source as a substrate for lipid production will help in reducing the overall cost of the production. The FAME, produced from oleaginous yeast, is useful as biodiesel feedstock [17].…”
mentioning
confidence: 99%
“…In this research, the titer of FAEE up to 82 mg/L was achieved by the supplementation of vegetable cooking oil (Ng et al, 2019). Meanwhile, Yu et al (2020) developed the synthetic co-culture system comprising the engineered S. cerevisiae and Y. lipolytica strain, which was able to produce FAEE at 4.8 mg/L. To overcome the limitation of oxidative stability in the traditional FAMEs, Markham and Alper (2018) first performed the production of C19 cyclopropanated fatty acids in the engineered Y. lipolytica strain, harboring the heterologous cyclopropane fatty acid synthase from E. coli.…”
Section: Biofuelsmentioning
confidence: 89%
“…Recently, by coculturing and engineered Y. lipolytica and S. cerevisiae strain, a synthetic microbial consortium was constructed to increase the titer of FAEE. In this research, the titer of FAEE biodiesel at 4.8 mg/L was reached by the synthetic microbial consortium under the optimum coculture conditions (Yu et al, 2020).…”
Section: Engineering Compartmentalization Systemmentioning
confidence: 92%
“…In the future, more ethanol biosynthetic pathway genes from different ethanologenic organisms need to be evaluated and introduced to our engineered R. toruloides strain to construct an endogenously ethanol-producing pathway. Recently, this proposed strategy was demonstrated to be feasible in the oleaginous yeast Y. lipolytica for the synthesis of FAEEs without the addition of ethanol, but the titer of produced FAEEs was quite low (0.3 mg/L) due to the limited supply of ethanol [28]. Thus, further efforts to increase the production of ethanol is required.…”
Section: Discussionmentioning
confidence: 99%